2015
DOI: 10.4238/2015.january.16.5
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype of Rhodnius montenegrensis (Hemiptera, Triatominae)

Abstract: ABSTRACT. The Triatominae subfamily comprises 6 tribes. The tribe Rhodniini comprises 2 genera and 22 nominal species. Rhodnius montenegrensis (Hemiptera, Triatominae) was recently described as evolutionarily related to R. robustus. Therefore, in order to contribute to karyosystematic study of the tribe Rhodniini, this report describes the number of chromosomes and compares the karyotype of R. montenegrensis to that of all other species in the tribe, in order to determine the karyotypic evolution of the tribe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…n. made it possible to describe the karyotype (2n = 22) and observe the constitutive heterochromatin pattern in the chromosomes (extremities of most autosomes), which are rich in CG. All the species in the tribe Rhodniini have 22 chromosomes (Alevi et al 2013, 2015b). On the other hand, out of the 14 species of the genus Rhodnius whose chromosomes have been studied in the literature, only four show heterochromatic blocks in the autosomes, namely R. colombiensis , R. nasutus , R. pallescens and R. pictipes (Dujardin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…n. made it possible to describe the karyotype (2n = 22) and observe the constitutive heterochromatin pattern in the chromosomes (extremities of most autosomes), which are rich in CG. All the species in the tribe Rhodniini have 22 chromosomes (Alevi et al 2013, 2015b). On the other hand, out of the 14 species of the genus Rhodnius whose chromosomes have been studied in the literature, only four show heterochromatic blocks in the autosomes, namely R. colombiensis , R. nasutus , R. pallescens and R. pictipes (Dujardin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The tribe Rhodniini consists of 22 species, 19 of which are from the genus Rhodnius and three of which are from Psammolestes (Abad-Franch et al 2013;Alevi et al 2013dAlevi et al , 2015. The species from the genus Rhodnius were grouped into specific complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic analysis also revealed that the tribe Rhodniini is a group in which the species vary little when compared to the common ancestor, since all of the species have the same chromosome number 2 n = 20A + XY (Pita et al 2013;Alevi et al 2013dAlevi et al , 2015 as their common ancestor (Ueshima 1966). Thus, new studies on these organisms are important for understanding the biology, evolution and classification of these vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Rhodnius includes 19 species (Alevi et al 2015), of which six were described after the publication of the Lent and Wygodzinsky review (1979): Rhodnius stali Lent, Jurberg & Galvão, 1993; Rhodnius colombiensis Mejia, Galvão & Jurberg, 1999; Rhodnius milesi (Carcavallo, Rocha, Galvão & Jurberg, 2001); Rhodnius zeledoni Jurberg, Rocha & Galvão, 2009; Rhodnius montenegrensis Rosa et al, 2012, and Rhodnius barretti Abad-Franch, Palomeque & Monteiro, 2013. Rhodnius amazonicus Almeida, Santos & Sposina, 1973 was synonymized with Rhodnius pictipes by Lent and Wygodzinsky (1979) according a photograph of the holotype, but subsequently it was validated by Bérenger and Pluot-Sigwalt (2002) by morphological study of 19 characters with of the two species.…”
Section: Introductionmentioning
confidence: 99%
“…This article describes Rhodnius marabaensis sp. n. as the tenth species found in northern Brazil and the twentieth member of this genus (Abad Franch et al 2013, Galvão 2014, Meneguetti et al 2014, Alevi et al 2015). …”
Section: Introductionmentioning
confidence: 99%